2016
DOI: 10.1007/s13277-016-5442-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miRNAs as non-invasive biomarkers for early diagnosis of lung cancers

Abstract: Current clinical diagnostic methods lack the specificity in detecting lung cancer patients. The issue is particularly critical for stage I and II patients. Considerable evidence showed microRNA plays a very important role in lung carcinogenesis. Here, we identified a panel of 41 miRNAs significantly elevated in patients with lung cancer, of which eight miRNAs were further validated in an independent sample cohort. Classification analysis using the panel of eight miRNAs generated a discriminatory power of 93.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…The remaining 216 articles were further checked by screening the full texts. Finally, a total of 134 studies from 65 articles including 13,983 samples (6,919 patients with lung cancer and 7,064 controls) were qualified for our analysis [ 11 75 ]. The process of article selection is summarized in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 216 articles were further checked by screening the full texts. Finally, a total of 134 studies from 65 articles including 13,983 samples (6,919 patients with lung cancer and 7,064 controls) were qualified for our analysis [ 11 75 ]. The process of article selection is summarized in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Most studies selected miRNAs by microarray [ 12 , 13 , 18 , 21 , 22 , 24 , 26 28 , 34 37 , 39 , 41 , 42 , 46 49 , 52 , 55 , 59 , 61 , 64 , 67 , 74 ]. Some identified miRNAs by literature [ 11 , 14 – 16 , 19 , 23 , 25 , 29 33 , 40 , 43 45 , 50 , 51 , 53 , 54 , 56 58 , 60 , 62 , 63 , 65 , 66 , 68 – 73 , 75 , 84 ]. To give an insight to future studies, we listed the potential miRNAs reported by literature that could serve as circulating biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 98 studies were included in 29 articles, and the number of patients with LC was 2487, and the number of included controls was 1467. The main characteristics of the included articles are listed in Tables S1‐S4.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen of the 20 studies provided no information on comorbidity of the patient cohort; the other 6 studies indicated that patients had no history of other cancers ( Supplementary Table 1A ) [ 26 , 48 52 ]. A mix of the two main subtypes of NSCLC, AC and SCC, was present in all the selected papers, however only in 11 studies the accuracy of the miRNA profile of NSCLC was separately evaluated for AC and SCC [ 26 , 29 , 30 , 41 , 44 , 46 , 48 50 , 53 , 54 ]. The composition of control groups was also varied ( Supplementary Table 1A ).…”
Section: Resultsmentioning
confidence: 99%